FORMULATION DEVELOPMENT AND EVALUATION OF NOVEL DUAL-COMPARTMENT CAPSULE FOR STOMACH SPECIFIC DRUG DELIVERY - Raysing, Swati D.; Rangari, Shyam; Sonawane, Uttara; Bari, Sanjay; Surana, Sanjay (Journal of Drug Delivery and Therapeutics, 2017)
The aim of the proposed research work was to develop a unique dual-compartment capsule dosage form of ciprofloxacin hydrochloride (CHL) which is well-known to have short elimination half-life and narrow absorption window. Formulated dual-compartment capsules were evaluated for its suitability for stomach specific drug delivery by employing different polymers such as Guar gum, Xanthan gum. Formulations were assessed for interaction studies, in vitro buoyancy, effect of polymer concentration on drug release and release kinetics. Experimental results demonstrated that natural polymers can be effectively exercised to formulate capsule dosage form for improved gastro retention and sustained drug release; which may be better and economic alternative for synthetic polymers.